2022
DOI: 10.3389/fonc.2022.1024173
|View full text |Cite
|
Sign up to set email alerts
|

Superficial vaginal myofibroblastoma with mushroom-like appearance: A case report with colposcopic findings and literature review

Abstract: Superficial myofibroblastoma (SMF) of the lower female genital tract is a relatively rare benign mesenchymal tumor. The diagnosis is usually challenging as it shares several similar clinicopathological features with other tumors. Herein, we present a case of a 71-year-old Chinese female patient with postmenopausal vaginal bleeding. Colposcopy imaging revealed a well-circumscribed mass in the vagina with a wide pedicle, resembling a mushroom. The patient underwent surgery, and the tumor was histologically diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Laskin et al reported 14 cases of subepithelial mesenchymal tumors in the female genital tract ( 1 ). Superficial cervical vaginal myofibroblastoma is rare with only 57 reported cases, involving the female genital tract ( 2 ). This was the first report of concomitant SCVM and endometrioid carcinoma in a patient with a history of breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Laskin et al reported 14 cases of subepithelial mesenchymal tumors in the female genital tract ( 1 ). Superficial cervical vaginal myofibroblastoma is rare with only 57 reported cases, involving the female genital tract ( 2 ). This was the first report of concomitant SCVM and endometrioid carcinoma in a patient with a history of breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Superficial myofibroblastomas are rare benign tumours of the female lower genital tract, with most cases reported in the literature occurring in the vagina 1–13…”
Section: Discussionmentioning
confidence: 99%
“…Superficial myofibroblastomas are rare benign tumours of the female lower genital tract, with most cases reported in the literature occurring in the vagina. [1][2][3][4][5][6][7][8][9][10][11][12][13] Here, we report a vulval superficial myofibroblastoma with an unusual finding of an inflammatory infiltrate consisting of lymphocytes and eosinophils at the rim and also within the tumour. While mast cells and lymphoid aggregates have been reported in superficial myofibroblastoma, we can find no existing report of an infiltrate of lymphocytes with rimming the tumour.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations